2021
DOI: 10.3171/2020.6.spine20863
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of telemedicine in spine surgery

Abstract: OBJECTIVEThe use of telemedicine (TM) has long been available, but recent restrictions to hospitals due to the coronavirus disease 2019 (COVID-19) pandemic have accelerated the global implementation of TM. However, evidence on the effectiveness of this technology for the care of spine surgery patients is limited. In this systematic review the authors aimed to examine the current utilization of TM for spine surgery.METHODSUsing PubMed, Scopus, and the Cochrane Library, the authors performed a systematic review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 31 publications
1
23
1
Order By: Relevance
“…Telemedicine usage among spine surgeons has rapidly risen in response to the novel coronavirus (COVID-19) pandemic and social distancing directives [1][2][3][4][5][6]. In a global survey investigating the impact of COVID-19 on spine surgeons, Louie et al [1] found that 35.6% of respondents were performing the majority of appointments via telemedicine by the end of the first quarter of 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine usage among spine surgeons has rapidly risen in response to the novel coronavirus (COVID-19) pandemic and social distancing directives [1][2][3][4][5][6]. In a global survey investigating the impact of COVID-19 on spine surgeons, Louie et al [1] found that 35.6% of respondents were performing the majority of appointments via telemedicine by the end of the first quarter of 2020.…”
Section: Introductionmentioning
confidence: 99%
“…In general, RCTs in eHealth are few despite occurrence of the COVID-19 pandemic situation, which has demonstrated a need for more evidence-based knowledge about the use of digital health technology in evaluating treatment effect, safety, and other aspects of patient management [34][35][36][37]. Patient education programs [38,39]; evaluation of psychological distress using teletechnology in diabetes [40]; use of mobile in suboptimal health [41], surgery care, and follow-up [42][43][44]; aphasia [44]; HIV consultations [38]; cancer symptom monitoring [45]; motor and cognitive function in stroke [46]; and COVID-19 follow-up [47] are areas where RCTs are used. Moreover, this study agrees with previous telemedicine RCTs in the same area reporting positive outcomes in treating diabetic foot ulcer [48] and in a follow-up study of orthopedic patients [49].…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…SPINE20 calls upon the G20 countries to expand telehealth for spine care, especially due to the current ongoing situation with COVID-19 [ 12 ]. By taking this measure, patients with spinal diseases can obtain timely advice toward alleviating pain and recognizing critical symptoms that need urgent care, and thus obtaining treatment in a timely manner [ 13 ].…”
Section: Introduction Of Spine20mentioning
confidence: 99%